Pola resistensi antimikroba pada infeksi saluran kemih yang disebabkan oleh bakteri penghasil ESBL dan non-ESBL - Lindayanti dr; Muzahar dr; Abdurrahim Rasyid Lubis (Fakultas Kedokteran USU, 2014)
Background : Urinary tract infection (UTI) is the most frequent infectious diseases occur and took second place after respiratory tract infections, where his first-line therapy is an antimicrobial. Many sufferers are not improved after treatment due to the onset of bacterial resistance to antimicrobials specific types and also the discovery of bacteria producing Extended-Spectrum BetaLactamase (ESBL). The aim of study is to determine the differences in patterns of antimicrobial resistance urinary tract infections caused by ESBL-producing bacteria and Non-ESBL.Methods : This study was an observational study with cross-sectional method included 50 outpatients in Departments of Internal Medicine Haji Adam Malik Hospital. Urinalisa examination found nitrites(+) or hematuria(+) or leukocytes> 10/lpb and continued urine cultures, Double Disk Synergy Test (DDST) and sensitivity test.Results : Antimicrobial resistance in ESBL groups were ampicillin (94.7%), and trimethoprim/sulfamethoxazole, ceftriaxon (84.2%), followed by cefotaxime, cefpodoxime and tetracyclin (78.9%) while in Non-ESBL group were ampicillin (88%), and trimethoprim/sulfamethoxazole (84%), and tetracyclin (76%). Differences patterns of antimicrobial resistance in E.coli ESBL producing group and Non-ESBL found cefotaxime significant (P = 0.021) and aztreonam significant (P = 0.031). Conclusion : ESBL-producing bacteria have an increased resistance to several antimicrobial mainly cephalosporin class although not statistically significantly different.Keywords : antimicrobial resistance; urinary tract infection; extended spectrum beta lactamase